Book Review. Nominalisasi Bahasa Prancis: Kaidah dan Kesulitan Pembelajarannya - Rio Rini Diah Moehkardi (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2017)
As stated by its author, Ferhadius Endi, his book is dedicated to Indonesian learners of French who often find difficulties in understanding French word formations, in particular the nominalization. Not only is French nominalization a complex word formation process, but also the fact that it is mostly explained in French references that give more difficulties for Indonesians learners to understand this particular area.